Pengembangan Soal Serupa Timss Untuk Mengukur Kemampuan Berpikir Kritis Dan Pemecahan Masalah Pada Konten Bilangan Kelas VIII - Wardani, Emi Kusuma; , Prof.Dr.Murtiyasa M.Kom (2016)
This research was purposed was to produce a valid and practical questions of TIMSS in number content. The method used in this research was a research and development method. This research required two phases, namely preliminary and formative evaluation phases which includes self evaluation, expert review, one-to-one, small group and field test. data collection technique used by walkthrough, document, and test. after going through one-to-one phase, small group, and field validation with descriptivematter in tested right at the stage of field test phase in class VIII SMP N 1 Colomadu. The test result overall with an average value of critical thinking abilities 56,8, can be categorized into good critical thinking ability, although there are still student who enter the category enough critical thinking ability. However, these result can also be said that the development of TIMSS model question categorized into valid and practical criteria and also has a potential effects on student's critical thinking abilities.